Origins and developments of the bibliography in the Order of Friars Minor Capuchin (Part II) - Francesca Nepori (Bibliothecae.it, 2019)
The essay reconstructs the history of the Capuchin bibliography whose origins are erroneously identified with the publication of the Bibliotheca of Dionisio da Genova, in 1680, or even with that of Bernardo da Bologna, in 1747. Through the study of the various bibliographies of the Order it was attempted to recognize the relationships that the bibliographies have between them (the ones following the previous ones) allowing to recover the ranks of Capuchin history to the present day.